2021
DOI: 10.1017/dmp.2021.244
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Psychological Health, Family Function, and Social Support During Their Third Trimester of Pregnancy Within the COVID-19 Epidemic: A Cross-sectional Survey

Abstract: Objective: The study aims to investigate women’s psychological health, family function, and social support during the third trimester within the COVID-19 epidemic. Method: From January 30, 2020 to February 26, 2020, 177 pregnant women during their third trimester (mean gestation time was 37.05±4.06 weeks) in a maternal and children’s hospital were investigated using the Self-Rating Anxiety Scale (SAS), the Edinburgh Postnatal Depression Scale, the Family APGAR Index, and the Perceived So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 8 publications
3
3
0
Order By: Relevance
“…Pregnant women may receive more support from their spouses who play an important role in preventing and alleviating the occurrence and development of mental disorders during pregnancy. Our results showed that pregnant women who spent more time with their partners during the pandemic had a lower risk of developing anxiety symptoms, which was consistent with the results of previous studies [ 36 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…Pregnant women may receive more support from their spouses who play an important role in preventing and alleviating the occurrence and development of mental disorders during pregnancy. Our results showed that pregnant women who spent more time with their partners during the pandemic had a lower risk of developing anxiety symptoms, which was consistent with the results of previous studies [ 36 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, our results verified that family function also had a direct impact on PRA. The study conducted by He in China is consistent with our result [ 64 ]. In a healthy family, family members can detect the psychological and physical changes of pregnant women, and provide timely material and spiritual help when women cope with anxiety or stressors [ 65 ].…”
Section: Discussionsupporting
confidence: 92%
“…The findings suggest that social support plays a mediating role between family adaptability and adolescent depression with an effect size of −0.085 ( Table 2 ). H2 was valid, which is consistent with He et al’s (2021) study that family adaptability is significantly and positively associated with social support. Individuals with high family adaptability have clear roles for their family members.…”
Section: Discussionsupporting
confidence: 89%